2017
DOI: 10.1177/0954008317745957
|View full text |Cite
|
Sign up to set email alerts
|

A novel curing agent based on diphenylphosphine oxide for flame-retardant epoxy resin

Abstract: A phosphorous/nitrogen-containing diphenylphosphine oxide (DPO) derivative (DPO-SS) was designed and synthesized via a two-step reaction of 4,4′-diaminodiphenylsulfone, 2-hydroxy-benzaldehyde, and DPO. The structure of DPO-SS was confirmed by Fourier transform infrared spectroscopy (FTIR), 1H and 31P nuclear magnetic resonance (NMR) spectroscopy, and mass spectrometry (MS). DPO-SS was used as a flame retardant and curing agent for copolymerizing with diglycidyl ether of bisphenol-A. Thermal and flame-retardant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
1
21
0
Order By: Relevance
“…The data presented in Figure A,C,E reveal that under a nitrogen atmosphere, all thermosets show a similar decomposition process. The introduction of EDPO, HTP‐6123, and HPCTP leads to a decrease in decomposition temperature of EP, which was also mentioned in other reports . The T 5% , T 10% , and T max of EP/EDPO‐P‐0.9 are 364°C, 374°C, and 409°C, respectively, while those for EP/HTP‐6123‐P‐0.9 are 365°C, 374°C, and 400°C, respectively, and those for EP/HPCTP‐P‐0.9 are 349°C, 358°C, and 378°C, respectively.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…The data presented in Figure A,C,E reveal that under a nitrogen atmosphere, all thermosets show a similar decomposition process. The introduction of EDPO, HTP‐6123, and HPCTP leads to a decrease in decomposition temperature of EP, which was also mentioned in other reports . The T 5% , T 10% , and T max of EP/EDPO‐P‐0.9 are 364°C, 374°C, and 409°C, respectively, while those for EP/HTP‐6123‐P‐0.9 are 365°C, 374°C, and 400°C, respectively, and those for EP/HPCTP‐P‐0.9 are 349°C, 358°C, and 378°C, respectively.…”
Section: Resultssupporting
confidence: 70%
“…Recently, diphenylphosphine oxide (DPO) and its derivatives have been used as flame retardants for EP in our group, and the performance of the flame retardant EPs were investigated . It was found that DPO or its derivatives modified diglycidyl ether of bisphenol A (DGEBA) EPs and led to good flame retardance performance.…”
Section: Introductionmentioning
confidence: 99%
“…At 25°C, the peaks at 3400, 2960, 2863, 1510, 1460, 1362, 1245, 1181, 1037, and 829 cm −1 are assigned to the typical absorptions of the epoxy matrix. 35 The relative intensity of the characteristic peaks of the epoxy resin declines sharply between 300°C and 500°C, indicating that the degradation of the epoxy thermosets occurred mainly in this temperature range. This phenomenon is consistent with the TGA results.…”
Section: Thermo-oxidative Degradation Behaviorsmentioning
confidence: 98%
“…[32][33][34] In our previous works, we concentrated on finding DPO derivatives-modified diglycidyl ether of bisphenol A (DGEBA) epoxy resins that showed apparent different properties compared with a similarly modified DOPO derivatives. 35,36 We realized that the molecular structure of DPO is similar to that of DOPO (Scheme 1), and each compound has an active P─H bond. The phosphorus content of DPO (15.32%) is a slightly higher than that of DOPO (14.33%), which means that lower dosage would be needed if DPO were to replace DOPO in the modification of epoxy resins.…”
Section: Introductionmentioning
confidence: 99%
“…Although phosphaphenanthrene flame retardants generally have high flame-retardant efficiency, low smoke and toxicity, they can influence the thermostability of epoxy resin significantly [11,15,22]. Recently, Wang et al applied DPO and its derivatives to flame retardants [23][24][25]. And Tian et al also applied DPO derivatives to flame retarded poly(ethylene terephthalate) [26].…”
Section: Introductionmentioning
confidence: 99%